2018
DOI: 10.1016/j.pharep.2018.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of brain natriuretic peptide signaling pathway in the cardioprotective action of sitagliptin

Abstract: The results of the present study suggest that the cardioprotective effect of sitagliptin is mediated partly, but not solely, through the BNP/cGMP/PKG survival signaling pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Even though the sensitivity and specificity are likely to be insufficient, both peptides are promising prognostic markers in acute coronary syndromes 23 . Moreover, the escalation of these peptides correlates with the severity of aortic stenosis and cardiac ischemia/reperfusion injury 24 , 25 . Interestingly, it was reported that BNP elevation correlates with suppressing the gene expression of endothelin (ET)-1 and prevents the stimulation of several hypertrophic kinases, such as protein kinase C (PKC) 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Even though the sensitivity and specificity are likely to be insufficient, both peptides are promising prognostic markers in acute coronary syndromes 23 . Moreover, the escalation of these peptides correlates with the severity of aortic stenosis and cardiac ischemia/reperfusion injury 24 , 25 . Interestingly, it was reported that BNP elevation correlates with suppressing the gene expression of endothelin (ET)-1 and prevents the stimulation of several hypertrophic kinases, such as protein kinase C (PKC) 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Nonhemodynamic factors such as catecholamines and other neuroendocrines synthesize BNP [31]. In pregnant women, the mechanism of BNP secretion is insufficiently understood, but BNP may be secreted by diuretic action to reduce the volume and pressure overload on the myocardial wall [32,33]. In the present study, in singleton pregnancies, the higher the BNP level immediately after childbirth was, the lower the E/e' at PP2 (Fig.…”
Section: Discussionmentioning
confidence: 49%
“…Nonhemodynamic factors such as catecholamines and other neuroendocrines synthesize BNP [31]. In pregnant women, the mechanism of BNP secretion is insu ciently understood, but BNP may be secreted by diuretic action to reduce the volume and pressure overload on the myocardial wall [32,33]. In the present study, in singleton pregnancies, the higher the BNP level immediately after childbirth was, the lower the E/e' at PP2 (Fig.…”
Section: Discussionmentioning
confidence: 49%